Assessing avionics-based GNSS integrity augmentation performance in UAS mission- and safety-critical tasks - Sabatini, Roberto; Moore, Terry; Hill, Chris; Ramasamy, Subramanian (2015)
The integration of Global Navigation Satellite System (GNSS) integrity augmentation functionalities in Unmanned Aerial Systems (UAS) has the potential to provide an integrity-augmented Sense-and-Avoid (SAA) solution suitable for cooperative and non-cooperative scenarios. In this paper, we evaluate the opportunities offered by this integration, proposing a novel approach that maximizes the synergies between Avionics Based Integrity Augmentation (ABIA) and UAS cooperative/non-cooperative SAA architectures. When the specified collision risk thresholds are exceeded, an avoidance manoeuvre is performed by implementing a heading-based differential geometry or pseudospectral optimization to generate a set of optimal trajectory solutions free of mid-air conflicts. The optimal trajectory is selected using a cost function with minimum time constraints and fuel penalty criteria weighted for separation distance. The optimal avoidance trajectory also considers the constraints imposed by the ABIA in terms of UAS platform dynamics and GNSS satellite elevation angles (plus jamming avoidance when applicable), thus preventing degradation or loss of navigation data during the Track, Decision and Avoidance (TDA) process. The performance of this Integrity-Augmented SAA (IAS) architecture was evaluated by simulation case studies involving cooperative and non-cooperative platforms. Simulation results demonstrate that the proposed IAS architecture is capable of performing high-integrity conflict detection and resolution when GNSS is used as the primary source of navigation data.